Legal Protection for Workers That Have Been Terminated Without Agreement - Arly, Ibnu; Khoironi, Ahmad (Budapest International Research and Critics University, 2021)
Manpower has an important role in the implementation of national development as actors and targets of national development based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Employment relationship is the relationship between workers and employers that occurs after a work agreement has elements of work, wages and orders. Thus, the employment relationship occurs because of a work agreement between the entrepreneur and the worker, where the work agreement can be made in writing or verbally, including a Work Agreement for a Specified Time (PKWT) and a Work Agreement for an Indefinite Time (PKWTT). Workers are workers who work in an employment relationship with employers by receiving wages. In Law Number 13 of 2003 concerning Manpower Article 51 it is stated that the employment agreement is made in writing or verbally. However, in reality there are many companies that do not comply with the provisions of the Manpower Act, workers who work without a work agreement under the Manpower Act will turn into PKWTT workers (permanent workers) for which the company is obliged to make a letter of appointment for the worker concerned. As a result of layoffs, workers will automatically lose their jobs which are a source of livelihood for them and their families. After being laid off to get their rights to employers is not easy and there is almost no legal effort for workers to refuse the layoffs, therefore workers who are laid off without an employment agreement must get legal protection so that their rights and obligations are fulfilled.